Wearable microsensor technology to measure physical activity demands in handball: a reliability study of inertial movement analysis and player load - Holme, B. R. (2015)
Purpose: Wearable microsensor technology allows for measurements of physical activity in team sports. To use this technology with confidence, it is critical to determine its reliability. Therefore, the purpose of this study was to assess the reliability and sensitivity of a commercially available microsensor technology to measure physical activity demands in handball. Methods: A total of twenty-two elite and sub-elite handball players (age, 22.6 ± 3.7 years; body mass, 84.0 ± 14.2 kg; height, 184.4 ± 12.0 cm; mean ± SD) were included in the present study. The subjects were instrumented with two devices (Optimeye S5, Catapult Sports, Melbourne, Australia), and participated either in a laboratory assessment (n =10) or field assessment (n = 12). The laboratory assessment consisted of seven different handball specific movement tasks, whereas the field assessment was conducted in twelve handball-training sessions. Various variables were extracted from the manufacture`s software (Catapult Sprint, Catapult Sports, Melbourne, Australia) including Inertial movement analysis (IMA) magnitude and counts, and tri-axial accelerometer data (Player Load). The reliability between devices and sensitivity was established using coefficient of variation (CV) and smallest worthwhile different (SWD). Results: Laboratory assessment: IMA magnitude showed a good reliability (2.9%) in well-controlled movement tasks. The CV increased (4.4 to 8.2%) in more chaotic movement tasks. Field assessment: IMA counts showed a good reliability (CV 2.4%) when displayed as total counts. However, the CV increased when categorized in low (2.9%), medium (5.5%) and high (5.6%) intensity bands. Medium/high band (combined) showed a CV of 3.9%. The CV for low, medium/high and total counts was less than the SWD. Furthermore, it was observed a good reliability of Player Load (0.9%), which was less than the SWD. Conclusion: The reliability of IMA counts was good, given that data were expressed as low, medium/high and total counts. It was observed a good reliability for Player Load. The CV of the aforementioned variables was well below the SWD, suggesting that Optimeye microsensors and its software are sensitive to detect "real and worthwhile" differences in handball activity.